Improving the Human Resources (HR) Capacity of Village Apparatus in the Field of Civil Law in Mediating Agrarian Conflicts: A Case Study in Grujugan Village, Cermee District, Bondowoso - Bustholil Arifin; Muhammad Abrori; Durrotul Masruroh; Gunvor Hallström (Aafiyah: Jurnal Multidisiplin Ilmu, 2024)
This research discusses the urgency of increasing the capacity of Human Resources (HR) of village officials in mediating agrarian conflicts over community land boundaries in Grujugan Village, Cermee Subdistrict, Bondowoso Regency in the aspect of non-litigation civil law related to agrarian conflicts. This research focuses on increasing the civil legal competence of village officials in their role as mediators and administrators of agrarian civil law conflicts experienced by village communities. The purpose of this research is to reveal the methods and strategies for increasing the capacity and civil legal competence of village officials in mediating agrarian conflicts. This research uses theoretical analysis of human resource capacity building in the village, village governance, agrarian civil law, and the search for relevant legal decisions. In addition, this research considers the impact of agrarian conflicts on the socio-economic conditions of the community, as well as the role of village heads and village officials in mediation and conflict resolution. Qualitative methods were used with data collection through observation, interviews, and literature study. The results showed that, first, the knowledge of the Grujukan village apparatus related to civil affairs is still low, especially in mediating agrarian conflicts experienced by its citizens. Secondly, there is no initiative from the village government in improving the competence and capacity of the village apparatus so that it has an impact on the role and function of the village apparatus as a mediator and conflict administrator in resolving conflicts.